2013
DOI: 10.1002/chem.201300284
|View full text |Cite
|
Sign up to set email alerts
|

Tetra(p‐tolyl)borate‐Functionalized Solvent Polymeric Membrane: A Facile and Sensitive Sensing Platform for Peroxidase and Peroxidase Mimetics

Abstract: The determination of peroxidase activities is the basis for enzyme‐labeled bioaffinity assays, peroxidase‐mimicking DNAzymes‐ and nanoparticles‐based assays, and characterization of the catalytic functions of peroxidase mimetics. Here, a facile, sensitive, and cost‐effective solvent polymeric membrane‐based peroxidase detection platform is described that utilizes reaction intermediates with different pKa values from those of substrates and final products. Several key but long‐debated intermediates in the perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…By selecting proper substrates, the enzyme activities can be determined by detecting ions generated by the enzymatic reactions using corresponding ISEs. Potentiometric assays for horseradish peroxidase [108], alkaline phosphate [109], butyrylcholinesterase [90], thrombin [110], and trypsin [111] are available. For example, Ding et al reported a simple, general and label-free potentiometric method to measure nuclease activities in a homogeneous solution using a polycation-sensitive membrane electrode [112].…”
Section: Enzymes and Proteinsmentioning
confidence: 99%
“…By selecting proper substrates, the enzyme activities can be determined by detecting ions generated by the enzymatic reactions using corresponding ISEs. Potentiometric assays for horseradish peroxidase [108], alkaline phosphate [109], butyrylcholinesterase [90], thrombin [110], and trypsin [111] are available. For example, Ding et al reported a simple, general and label-free potentiometric method to measure nuclease activities in a homogeneous solution using a polycation-sensitive membrane electrode [112].…”
Section: Enzymes and Proteinsmentioning
confidence: 99%
“…The potential change, which is closely related to the amount of LM, can be used for the quantification of LM. It should be noted that ophenylenediamine 34 and other C-derivatives of benzidine (such as N,N′,N,N′-tetramethylbenzidine, 3,3′-dimethoxybenzidine, and m,m′-ditolylamine) can also be used as the substrates for the developed methodology. 32 An original long peptide (WGEAFSAGVHRLAN) has been identified, which can recognize and capture the bacterial cells by interacting with the specific receptor on the membrane of LM to form a helical conformation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The potential change, which is closely related to the amount of LM, can be used for the quantification of LM. It should be noted that o -phenylenediamine and other C-derivatives of benzidine (such as N , N ′, N , N ′-tetramethylbenzidine, 3,3′-dimethoxybenzidine, and m , m ′-ditolylamine) can also be used as the substrates for the developed methodology …”
Section: Resultsmentioning
confidence: 99%
“…However, due to the irreversible nature of their response, these sensors are limited to single‐use devices. Recently, a novel polymeric membrane electrode‐based potentiometric sensing platform was reported for the detection of thrombin activity . This sensor was based on peroxide‐like DNAzyme function and was found to have high sensitivity and rapid regeneration.…”
Section: Introductionmentioning
confidence: 99%